Tissue engineering airway mucosa: A systematic review. (19th November 2013) - Hamilton, Nicholas; Bullock, Anthony J.; MacNeil, Sheila; Janes, Sam M.; Birchall, Martin
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Effective treatments for hollow organ stenosis, scarring, or agenesis are suboptimal or lacking. Tissue‐engineered implants may provide a solution, but those performed to date are limited by poor mucosalization after transplantation. We aimed to perform a systematic review of the literature on tissue‐engineered airway mucosa. Our objectives were to assess the success of this technology and its potential application to airway regenerative medicine and to determine the direction of future research to maximize its therapeutic and commercial potential. Data Sources and Review Methods A systematic review of the literature was performed searching Medline (January 1996) and Embase (January 1980) using search terms "tissue engineering" or "tissue" and "engineering" or "tissue engineered" and "mucous membrane" or "mucous" and "membrane" or "mucosa." Original studies utilizing tissue engineering to regenerate airway mucosa within the trachea or the main bronchi in animal models or human studies were included. Results A total of 719 papers matched the search criteria, with 17 fulfilling the entry criteria. Of these 17, four investigated mucosal engineering in humans, with the remaining 13 studies investigating mucosal engineering in animal models. The review demonstrated how an intact mucosal layer protects against infection and suggests a role for fibroblasts in facilitating epithelial regeneration in vitro. A range of scaffold materials were used, but no single material was clearly superior to the others. Conclusion The review highlights gaps in the literature and recommends key directions for future research such as epithelial tracking and the role of the extracellular environment. Laryngoscope, 124:961–968, 2014